NanR, a Transcriptional Regulator That Binds to the Promoters of Genes Involved in Sialic Acid Metabolism in the Anaerobic Pathogen Clostridium perfringens - Therit, Blair; Cheung, Jackie K.; Rood, Julian I.; Melville, Stephen B. (PLOS ONE, 2015)
Among many other virulence factors, Clostridium perfringens produces three sialidases NanH, NanI and NanJ. NanH lacks a secretion signal peptide and is predicted to be an intracellular enzyme, while NanI and NanJ are secreted. Previously, we had identified part of an operon encoding NanE (epimerase) and NanA (sialic acid lyase) enzymes. Further analysis of the entire operon suggests that it encodes a complete pathway for the transport and metabolism of sialic acid along with a putative transcriptional regulator, NanR. The addition of 30 mM N-acetyl neuraminic acid (Neu5Ac) to a semi-defined medium significantly enhanced the growth yield of strain 13, suggesting that Neu5Ac can be used as a nutrient. C. perfringens strain 13 lacks a nanH gene, but has NanI- and NanJ-encoding genes. Analysis of nanI, nanJ, and nanInanJ mutants constructed by homologous recombination revealed that the expression of the major sialidase, NanI, was induced by the addition of Neu5Ac to the medium, and that in separate experiments, the same was true of a nanI-gusA transcriptional fusion. For the nanI and nanJ genes, primer extension identified three and two putative transcription start sites, respectively. Gel mobility shift assays using purified NanR and DNA from the promoter regions of the nanI and nanE genes showed high affinity, specific binding by NanR. We propose that NanR is a global regulator of sialic acid-associated genes and that it responds, in a positive feedback loop, to the concentration of sialic acid in the cell.